雅虎香港 搜尋

  1. 我是傳奇/ F - one ~ 好多地方都有得買~香港仔ar~ mk~or ...

    目錄:娛樂及音樂 > 娛樂圈 2009年08月03日

  2. Question A bag contains n black balls and 20 white balls. If a ball is randomly drawn from the bag. the probability of drawing a black ball is 1/5. Find n. Solution There are (n+20) balls...

    目錄:科學及數學 > 數學 2013年08月30日

  3. 題目係咪漏左 d 野 ? 我當係呢條式 = 0 (X-3)^2 - 4x^2 = 0 將前面 (X-3)^2 變成 (x-3) (x-3), 乘開佢﹐成條式變成 : x^2 - 6x + 9 - 4x^2=0 -3x^2 - 6x + 9 = 0 兩邊都乘 -1 : 3x^2 + 6x - 9 = 0 兩邊都除 3 x^2 + 2x -3 = 0 拆番做答案 : (x+3)(x-1) = 0

  4. Some of the possible solutions are 75, 86, 97. First , you could write all the solutions, eg, 31, 42, 53, 64, 75, 86, 97and then cross out all the incorrect solutions.

    目錄:科學及數學 > 數學 2008年08月09日

  5. e種問題會比埋有邊2種coins,如果唔係唔會有答案,我就當係$5 coins吧 let the number of $2 coins be y , then we have the number of $5 coins be 135-y thus we have (135-y)(5)+(2)(y)=348 675-5y+2y=348 3y...

    目錄:科學及數學 > 數學 2013年07月21日

  6. 1a) x^2 +7x + 15 >0 since for x^2 +7x + 15 =0 have no real roots and a>0 x can be all real number 1b) 3x^2 -8x +6 ≤ 0 since for 3x^2 -8x +6 = 0 have no real roots and a>0 x have no real solution. 2010-10-03 12:35:19 補充: Given that an equation ax^2 +bx + c = 0 have no real root Case I...

    目錄:科學及數學 > 數學 2010年10月14日

  7. Cost of each oranges = $4000/5000 = $0.8 Selling price per orange at 40% discount on the cost = $0.8 x (1 – 40%) = $0.48 (a) Total income = 4000 x $1.2 + 1000 x $0.48 = $4800 + $480 = $5280 (b) Percentage of profit = (5280 – 5000)/5000 x 100% = 5.6%

    目錄:科學及數學 > 數學 2010年02月01日

  8. The final selling price is $850 x (1+35%) = $850 x 1.35 = $1147.5 Strategy 1: 10% discount was given, the marked-up price is $1147.5 / (1-10%) = $1147.5 / 0.9 = $1275 the marked price was increased by (1275- 1147.5)/1147...

    目錄:科學及數學 > 數學 2008年08月09日

  9. 1/(2+√3) <-[Times (2-√3) both numerator and denominator] =(2-√3)/[(2+√3)(2-√3) =(2-√3)/[2²-(√3)²] =(2-√3)/1 =2-√3

    目錄:科學及數學 > 數學 2011年09月06日

  10. 49 − (2x −1)2 = [7 + (2x −1)][7 − (2x −1)] = (2x + 6)(8 − 2x ) ==&gt; (2x + 6) = 2( x + 3) ==&gt; (8 − 2x ) = 2 (4 − x ) = 2( x + 3) X 2 (4 − x ) = (2X2)( x + 3)(4 − x ) = 4( x + 3)(4 − x )

    目錄:科學及數學 > 數學 2007年10月30日